2020
DOI: 10.18400/tekderg.476606
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Pavement Performance Based on LTPP Database for Flexible Pavements

Abstract: In many countries, incredible investments have been made in constructing roads that require conducting periodic evaluation and timely maintenance and rehabilitation (M&R) plan to keep the network operating under acceptable level of service. The timely M&R plan necessitates accurately predicting pavement performance, which is an essential element of road infrastructure asset management systems or Pavement Management Systems (PMS). Consequently, there is always a need to develop and to update performance predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Temperatures range from an average minimum of 6.60 • C in the winter to an average maximum of 36.9 • C in the summer. Beni-Suef receives fewer than eighty millimeters of precipitation annually in most areas [28,29]. The near-surface soil in this area is classified as Typic Torripsamments or Lithic Torripsamments [30].…”
Section: Location and Climatementioning
confidence: 99%
“…Temperatures range from an average minimum of 6.60 • C in the winter to an average maximum of 36.9 • C in the summer. Beni-Suef receives fewer than eighty millimeters of precipitation annually in most areas [28,29]. The near-surface soil in this area is classified as Typic Torripsamments or Lithic Torripsamments [30].…”
Section: Location and Climatementioning
confidence: 99%
“…In the observation category, the data collection is conducted using visual inspections by equipped modes of transport, e.g., automobile, bicycle [11][12][13][14][15][16], and intelligent monitoring techniques [17,18]. In addition, many pavement prediction models used the long-term pavement performance (LTPP) or short-term pavement performance (STPP) dataset to predict the future pavement performance [19][20][21].…”
Section: Data Sourcementioning
confidence: 99%
“…According to this paper achievement, it is observed from obtained result that the proposed neural network model for rutting depth has shown good agreement with experimental data. Radwan et al ( 22 ) developed ANN models for predicting fatigue and rutting distresses for wet and dry non-freeze climatic zones. When compared to the created statistical models, the results showed that the ANN technique can predict both distresses with high accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%